2019
DOI: 10.1503/cmaj.190221
|View full text |Cite
|
Sign up to set email alerts
|

Association between complications and death within 30 days after noncardiac surgery

Abstract: orldwide, 100 million patients aged 45 years and older undergo inpatient noncardiac surgery each year. 1,2 Although surgery has the potential to improve and prolong quality and duration of life, it is also associated with complications and mortality. During the last several decades, advances in perioperative care have included less invasive surgery, improved anesthetic techniques, enhanced intraoperative monitoring and more rapid mobilization after surgery. 2 At the same time, the age and the number of comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 24 publications
(13 reference statements)
2
103
1
6
Order By: Relevance
“…Such observation could also be explained by false negative COVID-19 results in suspected patients, potentially aligning their outcome to those of COVID-19 patients [ 25 ]. Overall, like other groups, we observed a moderately high 30-day postoperative mortality that was higher than expected in non-cardiac surgery (1–4%) [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 78%
“…Such observation could also be explained by false negative COVID-19 results in suspected patients, potentially aligning their outcome to those of COVID-19 patients [ 25 ]. Overall, like other groups, we observed a moderately high 30-day postoperative mortality that was higher than expected in non-cardiac surgery (1–4%) [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 78%
“…The Vascular Events in Non-cardiac Surgery Patients Cohort Evaluation (VISION) study found that 0.7% of deaths of adult patients who underwent non-cardiac surgery occurred in the operating room and 99.3% occurred after the procedure, with 29% occurring after discharge from hospital. The findings were reported in the Canadian Medical Association Journal 1…”
supporting
confidence: 52%
“…In low-care settings, such as surgical wards, the current standard is intermittent measurement of vital signs only, usually once every shift [ 1 , 2 ]. By contrast, when patients are discharged after major surgery, vital signs are no longer monitored at all, while it is known that more than 29% of deaths after noncardiac surgery occur after patients are discharged from the hospital [ 3 ]. Although the risk of patient deterioration has decreased by the time the patient is discharged from hospital, the risk that patient deterioration will go unnoticed increases.…”
Section: Introductionmentioning
confidence: 99%